Islamic Consumption Ethics: An Analysis of the Mukbang Phenomenon on Social Media - Faridatuz Zakiyah; Al-Ayyuubi, Mohammad Salahuddin (Faculty of Sharia and Islamic Economic, Universtas Annuqayah, 2025)
The global phenomenon of mukbang (eating broadcasts), characterized by the demonstrative consumption of excessive food portions, has become a profitable digital entertainment industry. However, this practice presents a deep ethical dilemma when viewed through the lens of Islamic consumption ethics, which strongly prohibit excessive behavior (israf) and waste (tabdzir). This study aims to analyze the fundamental principles of consumption ethics in Islam (halal, thayyib, and moderation) and to critically evaluate the practice of mukbang content within this ethical framework. Furthermore, it seeks to understand the impact of the mukbang phenomenon on the consumption behavior of its audience. This research employs a qualitative descriptive method using content analysis and library research. Data was collected from existing literature, scholarly articles on Islamic ethics, and case studies of popular mukbang content on social media platforms like YouTube. The analysis reveals a fundamental conflict between mukbang practices and Islamic principles. Mukbang inherently constitutes an act of israf’(excessiveness), directly contradicting Q.S. Al-A’raf: 31. It also raises concerns regarding the thayyib (goodness) principle, as it promotes consumption patterns detrimental to health, thus conflicting with the objective of hifdz al-nafs (preservation of life). Mukbang, while profitable as entertainment, normalizes gluttony and consumerism, potentially leading to negative societal and health impacts. This study concludes that the potential harm (mafsadah) of this phenomenon outweighs its claimed benefits (maslahah). It suggests a need for ethical guidelines for content creators and consumers in the digital age.